2019
DOI: 10.17305/bjbms.2018.4052
|View full text |Cite
|
Sign up to set email alerts
|

Teucrium Polium Plant Extract Provokes Substantial Cytotoxicity at the Early Stage of Embryonic Development

Abstract: The aim of this study is to explore the outcome of Teucrium polium (TP) medicinal plant consumption on the early stage of fetal development. We used the chicken embryo at 3 days of incubation as a model to evaluate the effect of TP plant extract during embryogenesis. In addition, quantitative polymerase chain reaction (qPCR) was applied to explore the expression of six genes related to cell proliferation, apoptosis, survival, angiogenesis, and migration. Our data revealed that TP exposure inhibits angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, the administration of aqueous rosemary extract without EO proved to be toxic through the inhibition of embryonic implantation [ 43 ]. Indeed, in ovo administration of plant extract has also been reported to have dramatic effects on embryonic development [ 44 ]. In addition, Bakkali et al [ 40 ] reported that essential oils have been shown to damage the cellular membrane structure as well as the cytoplasm and cell organelle membranes because of the great number of constituents.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the administration of aqueous rosemary extract without EO proved to be toxic through the inhibition of embryonic implantation [ 43 ]. Indeed, in ovo administration of plant extract has also been reported to have dramatic effects on embryonic development [ 44 ]. In addition, Bakkali et al [ 40 ] reported that essential oils have been shown to damage the cellular membrane structure as well as the cytoplasm and cell organelle membranes because of the great number of constituents.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TP extracts have antioxidant, antibacterial, and anti-inflammatory activities that can be explored for potential therapeutic uses. Recently, it has been reported that pregnant women could be very sensitive to these kinds of medical plants, especially in the early stage of pregnancy [ 18 ]. Therefore, the aim of the present study is to investigate the anti-inflammatory activity of TP extract to confirm its effectiveness in animal models.…”
Section: Introductionmentioning
confidence: 99%